2016
DOI: 10.1021/jacs.6b12246
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Ketone Monooxygenase from the Thermophilic Fungus Thermothelomyces thermophila: A Structurally Distinct Biocatalyst for Bulky Substrates

Abstract: Regio- and stereoselective Baeyer-Villiger oxidations are difficult to achieve by classical chemical means, particularly when large, functionalized molecules are to be converted. Biocatalysis using flavin-containing Baeyer-Villiger monooxygenases (BVMOs) is a well-established tool to address these challenges, but known BVMOs have shortcomings in either stability or substrate selectivity. We characterized a novel BVMO from the thermophilic fungus Thermothelomyces thermophila, determined its three-dimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 25 publications
2
58
0
1
Order By: Relevance
“…insertion of one atom of oxygen at the most‐ or least‐substituted position, respectively). BVMOs display a broad substrate scope,4, 5 which include cyclic ketones with a heteroatom,6, 7 macrocyclic ketones,8, 9, 10, 11 and substituted derivatives of various ring size (for example, terpene‐based substrates12, 13). 14, 15 BVMOs are also especially interesting in the synthesis of branched lactones, from which branched aliphatic polyesters with low glass transition temperatures can be made 16, 17, 18, 19, 20, 21, 22, 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…insertion of one atom of oxygen at the most‐ or least‐substituted position, respectively). BVMOs display a broad substrate scope,4, 5 which include cyclic ketones with a heteroatom,6, 7 macrocyclic ketones,8, 9, 10, 11 and substituted derivatives of various ring size (for example, terpene‐based substrates12, 13). 14, 15 BVMOs are also especially interesting in the synthesis of branched lactones, from which branched aliphatic polyesters with low glass transition temperatures can be made 16, 17, 18, 19, 20, 21, 22, 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…The lack of structural data, and poor alignments due to variation in the sequence length of the 'control loop' in these BVMOs, does however leave uncertainty as to the correlations between sequence and structure. Structural studies with polycyclic ketone monooxygenase (PockeMO) revealed a Tyr to occupy the equivalent position in structure space [20]. In an attempt to elucidate the role of Thr513 in the 'control loop' of BVMO AFL210 , we therefore turned to determining the structure using X-ray crystallography.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes : AcCHMO, RhCHMO, TmCHMO, and PsCPDMO were prepared as purified His‐PTDH‐fusion proteins as previously described . E. coli NEB 10 beta cells transformed with the pCRE‐BVMO plasmid were grown for 40 h at 24 °C shaking in Terrific Broth (TB) medium supplemented with ampicillin and 0.02 % l ‐arabinose.…”
Section: Methodsmentioning
confidence: 99%
“…The abnormal products have been reported, for example, on rac ‐bicyclo[3.2.0]heptanone and on terpenone precursors, and stand in contrast to chemical Baeyer–Villiger oxidations, which typically yield either the normal lactone (i.e., the lactone with substituents next to the ester group) or a mixture of both lactones . In the past decades, numerous BVMOs have been discovered and described, thereby broadening the substrate scope of this family of enzymes with macrocyclic ketones, bi‐ and tricyclic compounds, steroids, heteroatom‐containing ketones, and substituted cyclic ketones derivatives …”
Section: Introductionmentioning
confidence: 99%